Corrosion behavior of a compositionally complex alloy utilizing simultaneous Al, Cr, and Ti passivation. (June 2023) - Inman, Samuel B.; Sur, Debashish; Han, Junsoo; Ogle, Kevin; Scully, John R.
Abstract: The corrosion behavior of the Al0.3 Cr0.5 Fe2 Mn0.25 Mo0.15 Ni1.5 Ti0.3 compositionally complex dual-phase alloy was explored in a variety of electrolytes. Comparable corrosion resistance to 316L stainless steel and Ni-Cr binaries was observed in NaCl despite lower Cr concentrations. Individual elemental fates during corrosion were identified by combinations of in-situ atomic emission spectroelectrochemistry and ex-situ X-ray photoelectron spectroscopy with high-resolution surface analysis and depth profiling. A potentiostatically grown passive film was enriched in Al(III), Cr(III), Ti(IV), and Mo(VI). Al-Ti and Cr-Ti layers were suggested but significant Al, Cr, and Ti mixing was present. Proposed benefits of Al-Cr-Ti coexistence are addressed. Highlights: The passivation behavior and corrosion resistance of a dual-phase compositionally complex alloy is characterized. Elemental fates are tracked with X-ray Photoelectron Spectroscopy and Atomic Emission Spectroelectrochemistry. The effect of oxide aging on passive film composition and polarization resistance is evaluated. Intermixing of Al, Ti, and Cr within the passive film is observed without significant oxide layering. The benefits and drawbacks of Al and Ti are discussed with respect to light-weight compositionally complex alloy design.